Strategies for Optimizing QRIS Utilization to Strengthen the Financial Management of PKK Based Micro, Small, and Medium Enterprises in Kelapa Indah Village, Tangerang City - Sugiantoro Sugiantoro; Dede Lia Hernia; Dian Nazir Khan S; Rizka Cahya Purnama (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The advancement of digital technology has driven a transformation in payment systems from cash transactions to digital payments. The Quick Response Code Indonesian Standard (QRIS), established by Bank Indonesia, has emerged as a strategic innovation with significant potential to support financial management for Micro, Small, and Medium Enterprises (MSMEs). This community service activity (PKM) aims to enhance the knowledge and skills of PKK members running MSMEs in Kelapa Indah Village, Tangerang City, in utilizing QRIS as a digital payment system to support business financial management. Methods employed included counseling, training, mentoring, QRIS simulation, and evaluation of participants' comprehension before and after the activity. The program was conducted on June 7, 2026, with 14 MSME participants. Results showed significant improvements in participants' understanding of digital payment benefits, ease of QRIS usage, more organized transaction recording, and enhanced business financial management capabilities. QRIS adoption was proven to help MSMEs expand market access, increase customer trust, and minimize cash transaction risks. Optimizing QRIS usage can serve as an effective strategy to support digital transformation of PKK MSMEs and improve the quality of sustainable business financial management.